Mothers with under five children's knowledge and practices towards home management of diarrhoea in Lusaka district - Kosta, Gertrude Chipuka (Lusaka; University of Zambia, School of Medicine, 2007)
The study was conducted in two compounds of lusaka district; Misisi and kabwata. the aim of the study was to determine mother's/caretakers' of under five childrens knowledge and practices towards home management of diarrhoea.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Diarrhoea in children --Zambia.; Diarrhoea in children --Treatment --Zambia.